2017
DOI: 10.18632/oncotarget.15882
|View full text |Cite
|
Sign up to set email alerts
|

Regional structural impairments outside lesions are associated with verbal short-term memory deficits in chronic subcortical stroke

Abstract: Background and PurposeWe aimed to explore the neural mechanisms of verbal short-term memory (VSTM) impairment in subcortical stroke by evaluating the contributions of lesion and remote grey matter volume (GMV) reduction.ResultsThere was no significant correlation between lesions and VSTM. In stroke patients with left lesions, GMV reductions in the right middle frontal gyrus and in the left inferior frontal gyrus were positively correlated with VSTM impairment. In patients with right lesions, GMV reduction in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…Accordingly, the volumetric loss of the infratentorial regions may result from the Wallerian degeneration of the distal parts in the nervous systems following the injury of proximal axon or cell body (Yu et al, 2009). These results were in line with previous studies that reported the structural damage in remote regions in subcortical stroke, which was caused by axonal degeneration secondary to the occurrence of stroke lesions (Diao et al, 2017a, Diao et al, 2017b). However, volumetric alterations of infratentorial regions were rarely reported in patients with subcortical stroke.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Accordingly, the volumetric loss of the infratentorial regions may result from the Wallerian degeneration of the distal parts in the nervous systems following the injury of proximal axon or cell body (Yu et al, 2009). These results were in line with previous studies that reported the structural damage in remote regions in subcortical stroke, which was caused by axonal degeneration secondary to the occurrence of stroke lesions (Diao et al, 2017a, Diao et al, 2017b). However, volumetric alterations of infratentorial regions were rarely reported in patients with subcortical stroke.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the ratio of additional anatomical connections to missing connections was inverse in CI_L and CI_R groups, with more additional connections in CI_L groups and more missing connections in CI_R group. A previous study reported the right-sided stroke patients presented different cortical gray matter changes compared with left-sided ones (Diao et al, 2017a, Diao et al, 2017b), which also revealed a lesion-side effect, although they did not involve the volumetric changes of subcortical structures. This may also ascribe to the fact that right-handed patients with a left-dominant hemisphere stroke have less ability on daily life basis than those with lesions in the right hemisphere, which leading to faster degeneration of these regions in CI_L patients, as well as, the synergy volume alteration between the regions were more significant.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Our SVR-LSM analysis did not reveal any significant associations between lesion location and verbal memory impairment, which is consistent with previous findings. 38 These results suggest that the lesion itself may not be the critical neural mechanism for verbal memory impairment in the early phase of subcortical stroke in the area of the MCA. We found a significant positive correlation between the change rate of the left-thalamus volume and that of immediate recall, but not that of long-delay recall, in the left-hemisphere stroke patients within 12 weeks after onset.…”
Section: Discussionmentioning
confidence: 91%